Editor Cooperativo para Diagramação de Software OO - Dias, Márcio de Sousa; Xexéo, Geraldo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1997)
Complex software development requires an effective interaction among several specialists. This interaction can only be effective with the support of collaborative tools. This article presents a collaborative editor to support the diagramming activities of object oriented software modeling, describing the first version, where we exploited some synchronous aspects of the interaction.